Status Anak Kelahiran Perkawinan Tanpa Pencatatan Pemilikan Harta Warisan dari Ayah Biologis dalam Masyarakat Tionghoa di Kota Bagansiapiapi - Nurlaila, Nurlaila; Yefrizawati, Yefrizawati; Sembiring, Idha Aprilyana; Azwar, Tengku Keizerina Devi (Journal of Law & Policy Review, 2023)
In Kota Bagansiapiapi, it is common to find the Chinese community performing marriages based on their beliefs without registering them with the Civil Registry office. Divorce due to the death of the husband/father in such cases results in the marriage and child remaining unregistered. The unregistered child faces difficulties in inheriting paternal rights due to the lack of legal ties. This study aims to explore the mechanism of acknowledging children born from unregistered marriages within the Chinese community, the legal position of inheritance rights for children born from unregistered marriages, and the legal protection of a child's inheritance rights. The empirical research was conducted at the Vihara, the Civil Registration and Population Office, and Notaries in Kota Bagansiapiapi. The findings reveal the mechanism for acknowledging children and the implications of unregistered marriages on a child's inheritance rights. Legal protection for a child's inheritance rights remains fragmented and lacks harmonization with administrative regulations on population and marriage.